A study on customer satisfaction towards Pos Malaysia service during pandemic Covid-19 - Yuhanis Mohamed Noor,; Afifah Hanim Md Pazil,; Nurul Huda Hazizan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
University students were among those who had to study at home using online platforms, and they were strong Internet users during the recent COVID-19 pandemic. Furthermore, since COVID-19, the usage of the Internet and online transactions has become crucial. Hence, there is no doubt that the number of e-commerce platform users has increased, and online purchasing has expanded tremendously at the time. As online shopping grows in popularity, so do parcel and service delivery companies like Pos Malaysia Berhad. Pos Malaysia Berhad is a Malaysian courier company that provides services such as delivery, letter delivery, communication, financial, and supply chain management. Postal and courier services are one of the rapidly growing service businesses. On the other hand, customers struggle to find satisfaction when using the Pos Malaysia service. This study aimed to measure customer satisfaction with Pos Malaysia’s service quality. The quantitative design was used, and 110 undergraduates from public universities that use Pos Malaysia services were selected for this study, utilizing a convenience sample technique. The variables explored in this study include price, timely delivery, and response. The statistics package for social science (SPSS) software was used to analyze the data, which comprised descriptive and correlation analyses. According to the findings, customer satisfaction in Pos Malaysia is reasonable. However, service quality in Pos Malaysia is mediocre. Overall, the study found fairly significant relationships between customer happiness and the quality of services provided by Pos Malaysia.